Sentencing and criminal justice - Ashworth, Andrew; Kelly, Rory (Writer of Sentencing and criminal justice) (UK : Cambridge University Press, 2015)
"This revised and updated new edition focuses on major developments in sentencing law, practice and theory. Sentencing in England and Wales is now dominated by Sentencing Council guidelines, and scrutiny of those guidelines is central to this book. Issues of principle are identified and discussed, to include the constitutional position of the Sentencing Council; the meaning of, and challenges to, proportionality; and the sentencing of BAME offenders and women offenders. The book welcomes the new Sentencing Code, introduced as the Sentencing Act 2020, and critically examines the government's plans for sentencing reform, set out in the 2020 White Paper A Smarter Approach to Sentencing. Throughout the book, sentencing is explored in its wider criminal justice context - making it essential reading for courses on sentencing, criminal justice and criminal law"--
An introduction to English sentencing -- Sentencing, the sentencing council, and the constitution -- Sentencing aims, principles, and policies -- Proportionality and seriousness -- Aggravation and mitigation -- Equality before the law -- Custodial sentencing -- Non-custodial sentencing -- Persistence, prevention, and dangerousness -- Multiple offenders and totality -- Behaviour orders and ancillary orders, ancillary orders and civil preventive orders -- Special sentencing powers -- Procedural issues at sentencing -- Sentencing, guidelines, and the punitive state.
Includes bibliographical references (pages 459-477).
Keywords: Sentences (Criminal procedure) -- Great Britain; Punishment -- Great Britain